2015
DOI: 10.1089/ees.2014.0400
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lead in Water Associated with Iron Corrosion

Abstract: When attempting to reduce lead solubility by lowering the finished water pH in Providence, RI, from *10.3 to 9.7, consumer red water complaints and overall lead levels increased, prompting bench-scale tests and intensive field sampling into possible associations between higher particulate iron and particulate lead. At pH 10.3, iron release to water was as much as 35% lower in bench-scale tests and 99% lower in field samples compared with pH 9.7. Lower levels of particulate iron released at higher pH, translate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 28 publications
4
98
0
2
Order By: Relevance
“…A surprising degree of lead “removal” was actually adsorption by the plumbing materials, and the extent of this observed uptake was a function of the pH, which is in keeping with the strong sorption of lead to iron rust in the 4.0–8.0 pH range (Figure 7; Masters & Edwards 2015, Snoeyink & Wagner 1996). For example, the highest mean lead concentrations were observed in condition F samples (40% average recovery; Figure 6) and lowest mean concentrations in condition H samples (17% average recovery).…”
Section: Resultssupporting
confidence: 56%
“…A surprising degree of lead “removal” was actually adsorption by the plumbing materials, and the extent of this observed uptake was a function of the pH, which is in keeping with the strong sorption of lead to iron rust in the 4.0–8.0 pH range (Figure 7; Masters & Edwards 2015, Snoeyink & Wagner 1996). For example, the highest mean lead concentrations were observed in condition F samples (40% average recovery; Figure 6) and lowest mean concentrations in condition H samples (17% average recovery).…”
Section: Resultssupporting
confidence: 56%
“…Загвар дээр тулгуурлан хийсэн таамаглалын үнэмшилтэй байдал нь 50% дотор л байх юм. Энэхүү тодорхойгүй байдлыг үл хайхран энэхүү загвар нь дэлхий даяар хүлээн зөвшөөрөгдсөн учраас чухал байдаг [6].…”
Section: материал арга зүйunclassified
“…The presence of iron‐containing materials in drinking water distribution systems and premise plumbing can influence lead transport through several different scenarios (Table 1). In one scenario, iron oxide particles released from upstream water distribution pipes can deposit on the inner surfaces of LSLs (Deshommes, Laroche, Nour, Cartier, & Prévost, 2010; Masters & Edwards, 2015; Schock, Hyland, & Welch, 2008; Trueman & Gagnon, 2016b). These deposited iron particles can detach over time and facilitate the transport of lead to tap water (Deshommes et al, 2010; Lytle & Schock, 2005; Masters & Edwards, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In one scenario, iron oxide particles released from upstream water distribution pipes can deposit on the inner surfaces of LSLs (Deshommes, Laroche, Nour, Cartier, & Prévost, 2010; Masters & Edwards, 2015; Schock, Hyland, & Welch, 2008; Trueman & Gagnon, 2016b). These deposited iron particles can detach over time and facilitate the transport of lead to tap water (Deshommes et al, 2010; Lytle & Schock, 2005; Masters & Edwards, 2015). Two studies (Masters & Edwards, 2015; Trueman & Gagnon, 2016b) found that mixtures of particulate lead and iron were released from LSLs that contained previously deposited iron oxide particles.…”
Section: Introductionmentioning
confidence: 99%